2013
DOI: 10.1017/s0033291712003091
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of childhood psychotic symptoms for predicting schizophrenia by 38 years of age: a birth cohort study

Abstract: Background Childhood psychotic symptoms have been used as a subclinical phenotype of schizophrenia in etiological research and as a target for preventative interventions. However, recent studies have cast doubt on the specificity of these symptoms for schizophrenia, suggesting alternative outcomes such as anxiety and depression. Using a prospective longitudinal birth cohort we investigated whether childhood psychotic symptoms predicted a diagnosis of schizophrenia or other psychiatric disorders by 38 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
197
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(217 citation statements)
references
References 30 publications
(62 reference statements)
12
197
0
4
Order By: Relevance
“…First, the association between PE and suicidal ideation and behaviour has been investigated mostly in cross-sectional studies (Capra et al, 2015;DeVylder et al, 2015b;Jang et al, 2014;Kelleher et al, 2012c;Nishida et al, 2010;Saha et al, 2011;Temmingh et al, 2011), disabling causal inferences. Second, several studies included psychiatric diagnoses in the regression models to control for confounding (Calkins et al, 2014;DeVylder et al, 2015b;Fisher et al, 2013;Koyanagi et al, 2015;LewisFernandez et al, 2009;Olfson et al, 2002;Saha et al, 2011;Sharifi et al, 2015). However, it is conceptually impossible to examine a confounder in the association between PE and suicidal behaviour when that confounder, for example depression, is fundamentally associated with the outcome (Miller and Chapman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…First, the association between PE and suicidal ideation and behaviour has been investigated mostly in cross-sectional studies (Capra et al, 2015;DeVylder et al, 2015b;Jang et al, 2014;Kelleher et al, 2012c;Nishida et al, 2010;Saha et al, 2011;Temmingh et al, 2011), disabling causal inferences. Second, several studies included psychiatric diagnoses in the regression models to control for confounding (Calkins et al, 2014;DeVylder et al, 2015b;Fisher et al, 2013;Koyanagi et al, 2015;LewisFernandez et al, 2009;Olfson et al, 2002;Saha et al, 2011;Sharifi et al, 2015). However, it is conceptually impossible to examine a confounder in the association between PE and suicidal behaviour when that confounder, for example depression, is fundamentally associated with the outcome (Miller and Chapman, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several longitudinal studies have suggested that childhood psychotic symptoms may predict psychotic disorders in adulthood, 26,35,36 whereas other studies suggest a relatively good prognosis of psychotic symptoms in children. [37][38][39] It should be noted that most stimulantassociated psychotic symptoms were hallucinations and there is lack of consensus about the predictive value of hallucinations in children.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 On the other hand, PLEs that were overwhelmingly hallucinations predicted psychotic symptoms and disorders in adulthood in several large cohorts. 26,35,36,43 Although more data are needed on the longterm prognosis of hallucinations in childhood, recent reviews lean toward considering hallucinations in childhood as indicators of increased risk of adult psychiatric disorders. 44,45 At present, it is unclear if psychotic symptoms provoked by stimulant medication carry prognostic implications.…”
Section: Discussionmentioning
confidence: 99%
“…General population studies have found that 10-17% of children and 7.5% of adolescents report unusual experiences that are undistinguishable from delusions and hallucinations that occur in SMI (Kelleher et al 2012a, b). Psychotic symptoms in childhood are associated with family history of psychotic and mood disorders (Polanczyk et al 2010;Zammit et al 2013Zammit et al , 2014 and predict a range of psychiatric disorders in adulthood, including schizophrenia, other forms of SMI, as well as suicide attempts (Poulton et al 2000;Welham et al 2009;Fisher et al 2013). Therefore, psychotic symptoms in childhood and adolescence may represent early manifestations of liability, and understanding their underlying mechanisms may provide clues to the etiology and prevention of SMI.…”
Section: Introductionmentioning
confidence: 99%